Question : Find the average of odd numbers from 7 to 679
Correct Answer 343
Solution & Explanation
Solution
Method (1) to find the average of the odd numbers from 7 to 679
Shortcut Trick to find the average of the given continuous odd numbers
The odd numbers from 7 to 679 are
7, 9, 11, . . . . 679
After observing the above list of the odd numbers from 7 to 679 we find that the difference between two consecutive terms are equal. This means the list of the odd numbers from 7 to 679 form an Arithmetic Series.
In the Arithmetic Series of the odd numbers from 7 to 679
The First Term (a) = 7
The Common Difference (d) = 2
And the last term (ℓ) = 679
The average of the numbers forming an Arithmetic Series
= The first term (a) + The last term (ℓ)/2
⇒ The average of numbers forming an Arithmetic Series = a + ℓ/2
Thus, the average of the odd numbers from 7 to 679
= 7 + 679/2
= 686/2 = 343
Thus, the average of the odd numbers from 7 to 679 = 343 Answer
Method (2) to find the average of the odd numbers from 7 to 679
Finding the average of given continuous odd numbers after finding their sum
The odd numbers from 7 to 679 are
7, 9, 11, . . . . 679
The odd numbers from 7 to 679 form an Arithmetic Series in which
The First Term (a) = 7
The Common Difference (d) = 2
And the last term (ℓ) = 679
The Average of the given numbers
= Sum of the given numbers/Total number of given numbers
Thus, to find the average of the given numbers, first, we need to find their sum and the total number of given numbers
Finding the number of terms
For an Arithmetic Series, the nth term
an = a + (n – 1) d
Where
a = First term
d = Common difference
n = number of terms
an = nth term
Thus, for the given series of the odd numbers from 7 to 679
679 = 7 + (n – 1) × 2
⇒ 679 = 7 + 2 n – 2
⇒ 679 = 7 – 2 + 2 n
⇒ 679 = 5 + 2 n
After transposing 5 to LHS
⇒ 679 – 5 = 2 n
⇒ 674 = 2 n
After rearranging the above expression
⇒ 2 n = 674
After transposing 2 to RHS
⇒ n = 674/2
⇒ n = 337
Thus, the number of terms of odd numbers from 7 to 679 = 337
This means 679 is the 337th term.
Finding the sum of the given odd numbers from 7 to 679
The sum of all terms (S) in an Arithmetic Series
= n/2 (a + ℓ)
Where, n = number of terms
a = First term
And, ℓ = Last term
Thus, the sum of all terms (S) of the given odd numbers from 7 to 679
= 337/2 (7 + 679)
= 337/2 × 686
= 337 × 686/2
= 231182/2 = 115591
Thus, the sum of all terms of the given odd numbers from 7 to 679 = 115591
And, the total number of terms = 337
Since, the average of the given numbers
= Sum of the given numbers/Total number of given numbers
Thus, the average of the given odd numbers from 7 to 679
= 115591/337 = 343
Thus, the average of the given odd numbers from 7 to 679 = 343 Answer
Similar Questions
(1) Find the average of the first 2529 odd numbers.
(2) What is the average of the first 892 even numbers?
(3) Find the average of the first 2964 odd numbers.
(4) Find the average of odd numbers from 11 to 927
(5) Find the average of the first 2963 even numbers.
(6) Find the average of even numbers from 12 to 674
(7) Find the average of the first 2202 even numbers.
(8) Find the average of odd numbers from 5 to 429
(9) Find the average of the first 2893 odd numbers.
(10) What is the average of the first 32 even numbers?